Dialogue by short stories in the Renaissance: From courtly practice to urban play - I. K. Staf (Шаги, 2022)
The representation of oral narrative in Renaissance novella books involves not only references to literary sources, but also descriptions of social and cultural practices of the era. The framing model of The Decameron, converging with the Courtois Courts of Love and the jeux-partis, was partly reflected in the arrangement of Charles VI’s Court of Love in the early fifteenth century. One form of such aristocratic pastime, collective reading accompanied by singing, music, and dancing, influenced the activities of Italian “academies” in the 16th century. With the appropriation of this model of behaviour by urban literature, storytelling takes on the function of an exchange of news of a distinctly comic nature (Franco Sacchetti, Philippe de Vigneulles). The convergence between aristocratic and urban practices of recitation, reflected in particular in the titles of published novellas, brought to life — under the influence of the humanist tradition (Giovanni Pontano, Baldassare Castiglione) — the idea of the novella as a game, a collective performance, which was theorised in Girolamo Bargagli’s Dialogue on Games. The exchange of short stories can be considered one of the important practices of the era, the cultural content of which changed according to the historical and social context.